The User-Side Perspective on Implementing Electronic Health Records in Egypt - Romana, Nayrouz Ibrahim A. (AUC Knowledge Fountain, 2024)
Background: Electronic health records (EHR) have been recognized as an important tool to increase patient safety and overall improve efficiency in healthcare delivery. Despite this common knowledge, there is evidence that EHR has been slowly implemented in most developing countries. This research sought to identify factors that affect the adoption of EHR in Egypt from the perspectives of healthcare providers. Methods: This research was conducted in 2023 using mixed methodology. A self-administered questionnaire was sent to a sample of healthcare providers to assess their knowledge, attitude, and intention towards using the system. In addition, semi-structured interviews were conducted with experts in healthcare management to identify the barriers and facilitators of the implementation process. Results: A total of 177 healthcare providers completed the survey and seven experts were interviewed. A positive attitude, gender, and influence of subjective norms were found to be strong predictors of intention towards using EHR. Financial concerns, technical support, training, and data security were among the barriers affecting the adoption process. Conclusion: To the best of our knowledge, this is the first study conducted to examine the effect of perception factors on different healthcare professionals’ intention toward EHR adoption in Egypt using a mixed methodology. These findings could help healthcare organizations develop better EHR implementation strategies to increase the acceptance among the healthcare staff. Keywords: health professionals, Egypt, electronics health record system, knowledge, attitude, barriers